β-Arrestin 2 and ERK1/2 Are Important Mediators Engaged in Close Cooperation between TRPV1 and µ-Opioid Receptors in the Plasma Membrane - Melkes, Barbora; Markova, Vendula; Hejnova, Lucie; Novotny, Jiri (International journal of molecular sciences, 2020)
The interactions between TRPV1 and µ-opioid receptors (MOR) have recently attracted much attention because these two receptors play important roles in pain pathways and can apparently modulate each other's functioning. However, the knowledge about signaling interactions and crosstalk between these two receptors is still limited. In this study, we investigated the mutual interactions between MOR and TRPV1 shortly after their activation in HEK293 cells expressing these two receptors. After activation of one receptor we observed significant changes in the other receptor's lateral mobility and vice versa. However, the changes in receptor movement within the plasma membrane were not connected with activation of the other receptor. We also observed that plasma membrane β-arrestin 2 levels were altered after treatment with agonists of both these receptors. Knockdown of β-arrestin 2 blocked all changes in the lateral mobility of both receptors. Furthermore, we found that β-arrestin 2 can play an important role in modulating the effectiveness of ERK1/2 phosphorylation after activation of MOR in the presence of TRPV1. These data suggest that β-arrestin 2 and ERK1/2 are important mediators between these two receptors and their signaling pathways. Collectively, MOR and TRPV1 can mutually affect each other's behavior and β-arrestin 2 apparently plays a key role in the bidirectional crosstalk between these two receptors in the plasma membrane.
Keywords: MAP Kinase Signaling System; Receptors, Opioid; arrestiny; Morphine; Analgesics, Opioid; kationtové kanály TRPV; HEK293 Cells; lidé; TRPV Cation Channels; beta arrestiny; signální transdukce; receptory opiátové; Signal Transduction; HEK293 buňky; opioidní analgetika; beta arrestin 2; Receptors, Opioid, mu; Arrestins; fosforylace; receptory opiátové mu; morfin; buněčná membrána; beta-Arrestin 2; MAP kinasový signální systém; Phosphorylation; beta-Arrestins; Cell Membrane; Humans